Green synthesis and characterization of silver nanoparticles using aqueous petal extract of the medicinal plant Combretum indicum. (29th June 2016) - Bahuguna, Gaurav; Kumar, Amit; Mishra, Neeraj K; Kumar, Chitresh; Bahlwal, Aseema; Chaudhary, Pratibha; Singh, Rajeev
Abstract: For the first time, any type of plant extract from the medicinally important plant Combretum indicum has been used for the biosynthesis of silver nanoparticles (AgNPs). The present investigation reports the synthesis and characterization of AgNPs using the flower petal extract of Combretum indicum . For monitoring the formation and optical properties of the synthesized nanoparticles, they were analyzed using UV-visible spectroscopy. Apart from this, the luminescence properties were also studied by photoluminescence (PL) spectroscopy. Scanning electron microscopy (SEM) analysis revealed the formation of AgNPs and the surface morphology has been determined. The mean particle diameter using the dynamic light scattering (DLS) technique ranged from 50–120 nm depending upon the reaction time. The atomic percentage of Ag in synthesized NPs and the crystallinity were determined by energy dispersive x-ray (EDX) and x-ray diffraction (XRD), respectively. This green approach of synthesizing AgNPs, using a biologically important plant extract is found to be cost effective, economical, eco-friendly and convenient in synthesis.